Space and society in the 21st century. e case of São Paulo (2018)
The 21st century set new urban standards in relation to the demands of the population of the city of São Paulo. Economic growth, an increase in the population’s income and low unemployment have altered the political agenda of the city, which now has to address socio-spatial structures consolidated throughout history. From the urban and spatial point of view, there is still room for new critical assessments of the recent situation in which the largest metropolis in South America finds itself. In particiular with regard to the new urban practices which came to light during the 2013 protests. Recent economic and demographic indicators point toward a shift in the social geography of the city, which may result in significant impacts on its urban shape. The aim of this research is to investigate in detail the potential urban transformations emerging out of this new political and economic con guration. In order to do so, we highlight a number of urban and social phenomena which could lead to alternatives to the traditional administrative pacts (or those currently in force). This new condition points to speci c spatial di culties for urban planning and architecture, which go beyond the historical impediments already analyzed by the Brazilian critical tradition.